2020
DOI: 10.1080/09712119.2020.1746662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyme essential oil and A, C, and E vitamin combinations to diets on performance, egg quality, MDA, and 8-OHdG of laying hens under heat stress

Abstract: This experiment was conducted to evaluate the effects of supplementary thyme (Thymus vulgaris) essential oil (TEO) and A, C, and E vitamins on performance, egg quality and some biochemical parameters of laying hens under heat stress (HS). A total of 120 White Leghorn laying hens were randomly distributed into 5 experimental groups with 6 replicates and each replicate had 4 laying hens. The HS group was housed at 34°C between 08:00 am and 05:00 pm and the rest of the day at 22°C. The experimental groups were; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…One implication is the components of oregano oil, carvacrol and thymol, protect lipids and slow lipid peroxidation reactions from occurring as described by Botsoglou et al (2002) who supplemented broilers with dietary EOO. The finding in this study is in agreement with previous studies supplementing oregano oil on laying hens (Gul et al, 2019;Abo Ghanima et al, 2020;BüyükkılıçBeyzi et al, 2020).…”
Section: Antioxidant Capacitysupporting
confidence: 94%
“…One implication is the components of oregano oil, carvacrol and thymol, protect lipids and slow lipid peroxidation reactions from occurring as described by Botsoglou et al (2002) who supplemented broilers with dietary EOO. The finding in this study is in agreement with previous studies supplementing oregano oil on laying hens (Gul et al, 2019;Abo Ghanima et al, 2020;BüyükkılıçBeyzi et al, 2020).…”
Section: Antioxidant Capacitysupporting
confidence: 94%
“…Oxidative stress in broilers is associated with a high concentration of MDA and fatty acid peroxidation, due to increased free radicals [ 60 ]. Ginger has been shown to enhance antioxidative status.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Özek [ 33 ], the supplementation of the laying hens’ diets with essential oils, including Salvia officinalis and Origanum majorana , did not affect the product performance, apart from in terms of the egg weight and FCR, which was meaningfully higher in the treated groups than in the control group. Moreover, Bölükbası et al [ 34 ] showed that the inclusion of a 200 mg/kg extract of Salvia sclarea L. reduced the feed consumption of laying hens. In the latter study, the feed conversion was also improved in the hens supplemented with Salvia sclarea L., but there was no effect on the body weight or laying performance.…”
Section: Discussionmentioning
confidence: 99%